The effect of Bertholletia excelsa on body weight, cholestrol, and c-reactive protein: A systematic review and meta-analysis of randomized controlled trials. (March 2021) - Hou, Lili; Rashid, Muhammed; Chhabra, Manik; Chandrasekhar, Boya; Amirthalingam, Palanisamy; Ray, Sujoy; Li, Zhenzuo
Highlights: Bertholletia excelsa do not change body weight. Bertholletia excelsa reduces triglyceride and cholesterol levels. Bertholletia excelsa reduces LDL but no CRP. Abstract: Background & objective(s): Bertholletia excelsa is a rich herbal source of anti-oxidants and phenols. The goal of this study is to evaluation the effect of bertholletia excelsa nut on body weight, C-reactive protein (CRP) and lipid profile. Methods: A literature search was conducted in PubMed, Scopus and Web of sciences databases by two reviewers up to October 2019. Random effect model used to combine results. Results: Six studies included in analysis with 71 participants. The population was public population. Pooled results showed Bertholletia excelsa have reduction effect on triglyceride weighted mean difference (WMD: -8.23 mg/dl, 95 % CI -15.09, -1.38, I² = 0%), Cholesterol (WMD: -14.31 mg/dl, 95 % CI -23.38, -5.24, I² = 47 %), Low-density lipoprotein (LDL) (WMD: -9.27 mg/dl, 95 % CI -13.48, -5.06, I² = 0%). Conclusion: This study provided an evidence that Bertholletia excelsa nuts have reduction effect on triglyceride, cholesterol, and LDL levels.